Electron structure of the equilibrium and metastable phases in superionic Li₂SiS₃ - Bletskan, D.I.; Vakulchak, V.V.; Glukhov, K.E.; Mykaylо, O.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The calculations of a band structure E(k), the total N(E) and partial densities of electron states, as well as spatial distribution of the valence charge ρ(r) for the equilibrium (e) and metastable (m) phases of superionic Li₂SiS₃ were performed in a local approximation of the density functional theory (DFT) from the first principles for pseudopotentials in the basis of numerical pseudoatomic orbitals. The total density of states in the valence band calculated all over the Brillouin zone for both crystalline phases Li₂SiS₃ was compared to the experimental X-ray photoelectron spectra of the equilibrium, metastable and glassy phases. It is a good agreement between the calculation and experimental results for all bands of crystalline and glassy phases.